2022
DOI: 10.3389/fphys.2022.921709
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Acute Hypoxic Stress on Physiological and Hepatic Metabolic Responses of Triploid Rainbow Trout (Oncorhynchus mykiss)

Abstract: This experiment simulated the hypoxic environment caused by actual production operations in fish farming (i.e., catching, gathering, transferring, and weighting) to study the effects of acute hypoxic conditions on the physiological and metabolic responses of triploid rainbow trout (O. mykiss). Two groups of fish weighting 590 g were sampled in the normoxia group (dissolved oxygen above 7 mg/L) and hypoxia group (dissolved oxygen ranged from 2 to 5 mg/L for 10 min). The results showed that 1) regarding stress r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 52 publications
1
11
0
Order By: Relevance
“…Also, plasma glucose and lactate were increased at 1 h sampling time, showing a positive correlation with cortisol and recovering basal values 6 h after hypoxia. Similar results were observed in triploid rainbow trout by Han et al (2022), in turbot (Jia et al, 2021), and in rainbow trout exposed to acute stress hypoxia (4 mg O 2 /L) and crowding within 10 min (Pinedo-Gil et al, 2019). The absence of time effect on glycemic levels after hypoxia could be due to the fact that the stressor was not intense enough to induce sufficient gluconeogenesis and glycogenolytic action, or to the fact that one of the mediators of such response, catecholamines, shows a very quick response (Weendelar-Bonga, 1997), which did not help to detect significant changes at the sampling time assessed.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Also, plasma glucose and lactate were increased at 1 h sampling time, showing a positive correlation with cortisol and recovering basal values 6 h after hypoxia. Similar results were observed in triploid rainbow trout by Han et al (2022), in turbot (Jia et al, 2021), and in rainbow trout exposed to acute stress hypoxia (4 mg O 2 /L) and crowding within 10 min (Pinedo-Gil et al, 2019). The absence of time effect on glycemic levels after hypoxia could be due to the fact that the stressor was not intense enough to induce sufficient gluconeogenesis and glycogenolytic action, or to the fact that one of the mediators of such response, catecholamines, shows a very quick response (Weendelar-Bonga, 1997), which did not help to detect significant changes at the sampling time assessed.…”
Section: Discussionsupporting
confidence: 87%
“…On the contrary, Han et al (2022) found that sod, catalase, and gpx transcript levels in the liver from triploid rainbow trout were downregulated or unchanged after 10 min under hypoxia and crowding. These differences during hypoxia-reoxygenation could be due to species-, tissue-, and time-specificity, thus resulting in different dynamics.…”
Section: Discussionmentioning
confidence: 86%
“…Cells in living organisms adapt to hypoxia by changing metabolism, which is facilitated by changes in protein expression, mRNA or protein stability that occur at the level of transcription or translation (Solaini et al, 2010;. Multiple studies have clearly shown that oxygen homeostasis and iron metabolism are interlinked, such as the target of HIF, which play an important role in cell adaptation to low oxygen levels in normal and Frontiers in Physiology frontiersin.org damaged tissues, are involved in iron homeostasis (Shah and Xie, 2014;Xu et al, 2017;Yang et al, 2018;Han et al, 2022). The regulation between hypoxia and iron is complexed.…”
Section: Discussionmentioning
confidence: 99%
“…Fish fed the diet with the 6.6% lipid level had higher a-i HYP and total HYP contents than fish fed the diets with 14.8%, 22.8% and 29.4% (p < 0.05), while a-s HYP and PYD contents were not affected by dietary lipid levels (p > 0.05). 0.12 ± 0.01 0.10 ± 0.01 0.13 ± 0.01 0.14 ± 0.01 a-i HYP (mg/g muscle) 1 0.23 ± 0.02 a 0.01 ± 0.01 b 0.01 ± 0.00 b 0.01 ± 0.00 b Total HYP (mg/g muscle) 1 0.32 ± 0.03 a 0.11 ± 0.01 b 0.14 ± 0.01 b 0.15 ± 0.01 b PYD (μg/g muscle) 1 2.08 ± 0.11 2.12 ± 0.08 2.00 ± 0.14 2.03 ± 0.09…”
Section: Fillet Texturementioning
confidence: 99%
“…Rainbow trout (Oncorhynchus mykiss) is a globally farmed species. To avoid the degradation of fish quality associated with sexual maturation, triploid rainbow trout has been the main cold-water fish species cultured in China [1]. With the increase in production, fillet quality has become an important factor to determine consumer preference and sustainable development of aquaculture for the fish.…”
Section: Introductionmentioning
confidence: 99%